Merostachys tonicoi (Poaceae, Bambusoideae, Bambuseae), a new species at the frontier of Amazonian deforestation in Brazil - Lopes-Neto, Ray Balieiro; Schindler, Bianca; Figueira, Maurício; Simon, Marcelo Fragomeni; Vinícius-Silva, Ronaldo; Viana, Pedro Lage (Phytotaxa, 2025)
Recent collection efforts in the Rondônia state (Brazil) and inspection of Merostachys specimens in herbaria have revealed a distinct population of an Amazonian woody bamboo, here described and illustrated as a new species: Merostachys tonicoi. A morphological description, distribution, habitat and phenology data, a preliminary conservation status assessment, field photographs, a comparative table, taxonomic comments, and an identification key for the Brazilian Amazonian species of Merostachys are provided. Additionally, a comparative table and taxonomic comments on morphologically similar species from Eastern Brazil—M. delicatula and M. speciosa—are included.